Decentralization and the productive efficiency of government: evidence from Swiss cantons - Iwan Barankay; Benjamin Lockwood (Institute for the Study of Labor (IZA), 2006)
Advocates of fiscal decentralization argue that amongst other benefits, it can increase the efficiency of delivery of government services. This paper is one of the first to evaluate this claim empirically by looking at the association between expenditure decentralization and the productive efficiency of government using a data-set of Swiss cantons. We first provide careful evidence that expenditure decentralization is a powerful proxy for legal local autonomy. Further panel regressions of Swiss cantons provide robust evidence that more decentralization is associated with higher educational attainment. We also show that these gains lead to no adverse effects across education types but that male students benefited more from educational decentralization closing, for the Swiss case, the gender education gap.
urn:nbn:de:101:1-2008051627
Keywords: 330